Bearing capacity analysis of lightweight expanded clay aggregate (Leca) columns-raft under footing load - Zukri, Azhani (Books and Journals Private Ltd., 2021)
The major part of this paper is to present the LECA columns-raft load carrying capacity under footing load through three-dimensional finite element (FE) analysis. Instead of conventional aggregate for stone columns, lightweight expanded clay aggregate (LECA) has the potential to be used as replacement material. Using PLAXIS 3D, LECA raft and LECA column were modelled as Mohr-Coulomb material and the nonlinear behavior of soft soil is modelled with Soil Hardening constitutive model. The LECA columns are assumed to be ‘wish in place’, where possible smear effects caused by disturbance on the surrounding soil due to column installation effect is ignored. The column diameter and soft soil depth used in the study were 700mm and 10 meters, respectively. The laboratory tests were carried out to identify the engineering properties of kaolin clay (represent the soft clay layer) and LECA material. From the finite element analysis, it was noticed that ability of soft soil replacement by LECA aggregates to improve the bearing capacity of footing on soil. The ultimate load carried by the LECA columns-raft increases by decreasing LECA column spacing, increasing the raft thickness and length of LECA columns. The load carrying capacity of the LECA columns-raft increases with increasing L/D (column length to diameter ratio) up to a certain ratio. The FE analysis revealed that for L/D greater than 6, the increment in the ultimate load for all raft thickness are negligible. Thus, it is not necessary to construct end bearing LECA columns with the LECA raft due to the small difference between bearing capacity and the other lengths of LECA columns. It is also proved that LECA columns with higher replacement ratio do not necessarily require a thick raft replacement. Several physical modelling were conducted in order to validate the results from numerical modelling. Ultimate bearing capacity was evaluated using 2D chamber. Form the physical modelling, it was found that the error percentage of ultimate bearing capacity in which the difference was contributed by the over prediction of numerical analysis. Nevertheless, based on the comparison of the results, the maximum difference is 11.5%, which is less than 12% and is in good agreement.